2011
DOI: 10.1186/1475-2859-10-s1-s19
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the stress responses of probiotics for a lifestyle from gut to product and back again

Abstract: Before a probiotic bacterium can even begin to fulfill its biological role, it must survive a battery of environmental stresses imposed during food processing and passage through the gastrointestinal tract (GIT). Food processing stresses include extremes in temperature, as well as osmotic, oxidative and food matrix stresses. Passage through the GIT is a hazardous journey for any bacteria with deleterious lows in pH encountered in the stomach to the detergent-like properties of bile in the duodenum. However, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 136 publications
(126 reference statements)
3
121
0
4
Order By: Relevance
“…During transit through the GIT, several Lactobacillus spp. survive the low pH of the stomach (pH 2.0 to 4.0) and the subsequent exposure to bile salts and pancreatic juice in the duodenum (27). Lactobacillus spp.…”
Section: Common Stresses Encountered By Lab In Their Ecological Nichesmentioning
confidence: 99%
See 1 more Smart Citation
“…During transit through the GIT, several Lactobacillus spp. survive the low pH of the stomach (pH 2.0 to 4.0) and the subsequent exposure to bile salts and pancreatic juice in the duodenum (27). Lactobacillus spp.…”
Section: Common Stresses Encountered By Lab In Their Ecological Nichesmentioning
confidence: 99%
“…They encounter a variety of stresses during production and use. Before a probiotic bacterium begins to fulfill its biological role in the gut, it must survive a battery of environmental challenges (27). Initially, probiotic bacteria must be processed in a suitable product form to enable oral consumption in adequate numbers, and then the bacteria must survive the harsh conditions imposed during passage through the GIT (451).…”
Section: Stress Mechanisms In Probiotic Labmentioning
confidence: 99%
“…The main gastrointestinal stress factors are considered to be the acidic environment of the stomach and the presence and effect of bile salts in the duodenum (Mills, Stanton, Fitzgerald, & Ross, 2011). Gorbach and Goldin (1989) showed that Lactobacillus rhamnosus GG decreased from 10 8 to 10 6 after 0.5 h at pH 2.5 in normal human gastric juice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, microbial preadaptation at different temperatures or at different solute concentrations could increase the strain resistance to some stress conditions during drying and storage [232]. However, this type of studies was not published for vaginal probiotic microorganisms.…”
Section: Storage Of Api Of Interest and Formulation Of Urogenital Promentioning
confidence: 99%